2014
DOI: 10.1177/1053815115569732
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Quality of Inclusive Practices

Abstract: The purpose of this study was to test the reliability and validity of the Inclusive Classroom Profile (ICP), an observation measure designed to assess the quality of classroom practices in inclusive preschool programs. The measure was field tested in 51 inclusive classrooms. Results confirmed and extended previous research findings, providing further evidence for the measure's interrater reliability, factor structure, and construct validity. New information from testing the relationship between the ICP and key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 10 publications
0
11
0
3
Order By: Relevance
“…At least one study has reported differences in inclusion quality across program types, meaning the authors found differences in the quality of practices specific to the education and inclusion of children with disabilities. Soukakou, Winton, West, Sideris, and Rucker (2014) found that center-based childcare programs had significantly lower Inclusive Classroom Profile (ICP) scores compared with public school, Head Start, and reverse mainstreaming preschool classrooms. The significant difference between childcare ICP scores and the other programs remained when controlling for teacher education, Early Childhood Environment Rating Scale–Revised (ECERS-R) scores, special education course hours, and the number of children with an Individualized Education Program (IEP).…”
Section: Examining the Diverse Contexts Of Inclusive Education: Revismentioning
confidence: 99%
See 2 more Smart Citations
“…At least one study has reported differences in inclusion quality across program types, meaning the authors found differences in the quality of practices specific to the education and inclusion of children with disabilities. Soukakou, Winton, West, Sideris, and Rucker (2014) found that center-based childcare programs had significantly lower Inclusive Classroom Profile (ICP) scores compared with public school, Head Start, and reverse mainstreaming preschool classrooms. The significant difference between childcare ICP scores and the other programs remained when controlling for teacher education, Early Childhood Environment Rating Scale–Revised (ECERS-R) scores, special education course hours, and the number of children with an Individualized Education Program (IEP).…”
Section: Examining the Diverse Contexts Of Inclusive Education: Revismentioning
confidence: 99%
“…A set of detailed quality indicators accompanies each item. Although the ICP is still a relatively new measure, initial validation studies are promising (Soukakou, 2012; Soukakou et al, 2014). Like other inclusion quality measures, the ICP only assesses classroom features and practices unique to the education of young children with disabilities—it does not include global quality indicators.…”
Section: Defining and Measuring Quality In Inclusive Early Childhood mentioning
confidence: 99%
See 1 more Smart Citation
“…The proceeding on what quality mainstreaming is and how it should be applied resulting from the long-lasting experiences based on preschool mainstreaming practices, prepared by the two major organizations, namely DEC and NAEYC, have been put in the literature (Division for Early Childhood National Association for the Education for Young Childen, 2009). With this proceeding, the concepts of "Access, Participation and Support" that determine the quality of mainstreaming practices in preschool education have been explained, and field experts have agreed on a common opinion on their placement in preschool education standards (Larocco & Barton, 2016;Odom, Buysse, & Soukakou, 2011;Soukakou, Winton, West, Sideris, & Rucker, 2015).…”
Section: Explore Importance Of the Problemmentioning
confidence: 99%
“…Using observational assessments to collect data on classroom and teacher variables that contribute to education quality is well-established in preschool research (Pianta et al 2005; Reszka et al 2012; Sam et al 2015; Westman Andersson et al 2013). Several assessments of general early childhood education environments, such as the Early Childhood Environment Rating Scale-Revised (Harms et al 2005; Kärrby 1989; Kärrby and Giota 1994), and the Inclusive Classroom Profile (Lundqvist et al 2016; Soukakou 2012; Soukakou et al 2014) are examples of scales that have been developed and translated to Swedish. However, there is to date no instrument available in Swedish designed to assess the quality of the intervention program setting for preschool children with ASD.…”
mentioning
confidence: 99%